Pengaruh Harga Pupuk dan Harga Jual Terhadap Keberlanjutan Usaha Tani Melalui Kualitas Apel di Desa Andonosari Kecamatan Tutur Kabupaten Pasuruan - Yulia Nor Frassiska; Mochamad Taufiq; Purwaningrum Puji Lestari (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the influence of fertilizer prices and selling prices on the sustainability of apple farming, with apple quality serving as a mediating variable. The research was conducted in Andonosari Village, Tutur District, Pasuruan Regency, which is one of the main apple-producing areas in East Java. A quantitative approach with path analysis techniques was employed to determine both direct and indirect relationships among the variables. Data were collected from 96 apple farmers using structured questionnaires. The findings indicate that fertilizer prices do not have a direct effect on the sustainability of apple farming. However, fertilizer prices significantly affect apple quality, which in turn indirectly influences the sustainability of farming activities. Meanwhile, selling prices have a significant direct impact on both apple quality and the sustainability of apple farming. These results demonstrate that apple quality acts as an important mediating factor between fertilizer prices and selling prices in maintaining sustainable farming practices. Therefore, improving apple quality is a key strategy to strengthen the sustainability of apple farming, especially in facing the challenges of fluctuating fertilizer and market prices. This study provides useful insights for policymakers and farmers in developing strategies to enhance productivity and sustainability in apple agribusiness.